2007
DOI: 10.1101/gad.1544207
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-dependent H3K27 methylation is required for heterochromatin formation and DNA elimination in Tetrahymena

Abstract: Methylated H3K27 is an important mark for Polycomb group (PcG) protein-mediated transcriptional gene silencing (TGS) in multicellular eukaryotes. Here a Drosophila E(z) homolog, EZL1, is characterized in the ciliated protozoan Tetrahymena thermophila and is shown to be responsible for H3K27 methylation associated with developmentally regulated heterochromatin formation and DNA elimination. Importantly, Ezl1p-catalyzed H3K27 methylation occurs in an RNA interference (RNAi)-dependent manner. H3K27 methylation al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
351
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(377 citation statements)
references
References 78 publications
20
351
1
5
Order By: Relevance
“…However, these studies could not address identification of specific repressive histone marks as the reagents for the study were not available. It has been reported in other biological systems that enrichment of methylated H3K27 associates with gene repression (14,43). Using newly generated reagents, we have identified that E. histolytica also contains this repressive epigenetic mark, which deposits at RNAi-silenced loci.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, these studies could not address identification of specific repressive histone marks as the reagents for the study were not available. It has been reported in other biological systems that enrichment of methylated H3K27 associates with gene repression (14,43). Using newly generated reagents, we have identified that E. histolytica also contains this repressive epigenetic mark, which deposits at RNAi-silenced loci.…”
Section: Discussionmentioning
confidence: 88%
“…However, conserved lysine residues, which are targets for post-translational modifications, are maintained in the E. histolytica histone H3 tail. In higher eukaryotes, enrichment of methylated H3K27 is associated with gene repression (13,14,43,44). Hence, we asked whether coupling of H3K27 methylation and transcriptional gene silencing is conserved in E. histolytica.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct roles of small RNAs in the propagation of heterochromatin have been established in several eukaryotic systems, including Tetrahymena, fission yeast, and Drosophila (Moazed et al 2006;Zofall and Grewal 2006;Liu et al 2007). However, the case remains unresolved in mammalian cells, in large part due to the difficulty of detecting small RNAs homologous to heterochromatin regions, especially in somatic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similar processes are involved in heterochromatin formation and programmed DNA elimination in ciliates, (35,36) as well as heterochromatin formation and nucleolar organization in Drosophila. (18,37) The nuclear organization of chromatin insulators and chromatin domains is also affected by the RNAi machinery (38) and recent deep sequencing studies have…”
Section: Introductionmentioning
confidence: 99%